METODOLOGI DAN KRITERIA KRISTOLOGI - Cecen; Ronald Evandi Aden; Yongki Pransoli; Sarmauli (Pojok Publisher, 2025)
This study discusses the methodology and development of Christology from the early church era to the perspective of contemporary theology. The focus of the study includes the influence of Old Testament prophecy on the understanding of Jesus Christ, the deviations in teachings that emerged, and the important role of the Councils of Ephesus and Chalcedon in forming orthodox Christology. The research method used is qualitative with a descriptive-analytical approach through literature studies. The results of the study show that Christology has experienced significant developments that are inseparable from historical and theological challenges, including the struggle in understanding the relationship between the divinity and humanity of Jesus. In addition, the doctrine of the Trinity provides an important foundation for the formation of a comprehensive and contextual Christology, especially in answering the needs of Christian faith today.